Investigation on the Influence of Design Parameters of Streamline Flow Tubes on Pump Performance - Kan Bian; Zhi Huang; Jietao Dai; Fan Zhang; Xiaosheng Chen; Zhenlin Chen; Liyi Lai; Jianhui Zhang (Shock and Vibration)
Studies have shown that the valveless piezoelectric pump with streamline flow tubes (VPPSFTs) can increase the flow rate while reducing the vortex, which has a broad application prospect and conforms to the huge potential demand in the fields of medical treatment, sanitation, and health care. The flow runner of the VPPSFT was designed as two segments with a smooth transition between the hyperbola segment and the arc segment. However, the effect of the radius of the arc segment on pump performance is not clear. Therefore, three groups of VPPSFT with arc segments of different curvature radii were designed in this study, and the influence of curvature radius of arc segment on the pump performance was explored. On the basis of the theoretical analysis of fluid continuity and conservation of energy, the structure of VPPSFT was designed, the experimental test was carried out, and the finite element simulation software was used for numerical analysis. The results show that the output performance increases with the increase in the radius of the arc segment, and the maximum flow rate was 116.78 mL/min. The amplitude and the flow rate are almost the same trend as the frequency. This study improves the performance of the valveless piezoelectric pump and provides reference for the structure design of VPPSFT.